2012
DOI: 10.4103/0974-9233.95266
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent macular corneal dystrophy and keratoconus

Abstract: A 21-year-old female presented with progressive bilateral visual loss for the past 8 years. The patient had no history of systemic disease, surgery or medications. Complete ophthalmologic examination and topography were performed. On ophthalmic examination, uncorrected visual acuity was counting fingers at 2.5 m (20/50 with pinhole) in the right and left eyes. Both corneas appeared hazy on gross examination. On slit-lamp biomicroscopy, focal grayish-white opacities with indistinct borders were noted in the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The cornea of MCD patients is typically thinner, leading to a significantly lower CV. While most patients with MCD do not exhibit corneal ectasia there are case studies in the literature that have linked keratoconus to MCD (16)(17)(18) . Both keratoconic and MCD corneas exhibit reduced keratan sulfate concentrations and an elevated dermatan to keratan sulfate ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The cornea of MCD patients is typically thinner, leading to a significantly lower CV. While most patients with MCD do not exhibit corneal ectasia there are case studies in the literature that have linked keratoconus to MCD (16)(17)(18) . Both keratoconic and MCD corneas exhibit reduced keratan sulfate concentrations and an elevated dermatan to keratan sulfate ratio.…”
Section: Discussionmentioning
confidence: 99%
“…There are few case reports on the cooccurrence of keratoconus and MCD [ 37 , 38 ]. In the study of Dudakova et al, the authors observed anterior, paracentral steepening of the corneal surface, which was graded as keratoconus by Scheimflug integrated software, but without a coexisting ectasia pattern on the posterior corneal surface [ 28 ].…”
Section: Discussion and Csonclusionsmentioning
confidence: 99%